A contemporary, nationwide analysis of surgery and radiotherapy treatment for prostate cancer. (5th September 2019) - Roberts, Matthew J.; Papa, Nathan; Perera, Marlon; Scott, Susan; Teloken, Patrick E.; Joshi, Andre; Vela, Ian; Pryor, David; Martin, Jarad; Woo, Henry
Abstract : Objective: To characterize national clinical practice trends in the treatment of prostate cancer (PCa) in Australia. Patients and Methods: Population‐level data were extracted from existing Medicare Benefits Schedule data for radical prostatectomy (RP) and brachytherapy (2002–2016), as well as external beam radiotherapy (EBRT; 2012–2016). Treatment rates were calculated relative to whole and PCa populations among privately treated patients. Overall age‐related and geographical trends were analysed. Results: The use of RP and low‐dose‐rate (LDR) brachytherapy increased between 2002 and 2009, but subsequently decreased to 124 and 6.9 per 100 000 men, respectively, in 2016. More dramatic decreases were observed for men aged <65 years. From 2012, rates of RP (15% drop) and LDR brachytherapy (58% drop) decreased, while the use of EBRT remained steady, falling by 5% to 42 per 100 000 men in 2016. Overall treatment increased in the age group 75–84 years, with the rate of RP increasing by 108%. Conclusion: National claims data indicate there has been a reduction in PCa treatment since 2009, which is mostly attributable to a reduction in the treatment of younger patients and reduced use of brachytherapy. RP is most commonly used and its use is rising in men aged >65 years.